2022
DOI: 10.1007/s40489-022-00335-5
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Health Promotion and Obesity Prevention for Children and Adolescents with Developmental Disabilities: a Systematic Review

Abstract: This systematic review evaluated interventions and relevant outcomes for health promotion and obesity prevention among children and adolescents with developmental disabilities (DD). Twenty-one studies including randomized control trials ( n = 9) and quasi-experimental studies ( n =12) published between 2010 and 2021 met inclusion criteria related to participant characteristics, intervention type, and child obesity-related outcomes. Five types of intervention progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…For example, an adolescent with picky eating may have increased food acceptability when eating out or traveling; if these activities decrease stress, they may be more important than adding new, healthier food choices. Multifactorial causes of weight gain in the patient with SHCN include picky eating, compulsive behaviors, restrictive eating (often due to texture), dysregulated eating patterns, lack of access to adaptive physical activity, decreased metabolism, and iatrogenic weight gain (especially antipsychotic medication) [ 28 , 35 , 36 ].…”
Section: The Adolescent With Special Healthcare Needs and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an adolescent with picky eating may have increased food acceptability when eating out or traveling; if these activities decrease stress, they may be more important than adding new, healthier food choices. Multifactorial causes of weight gain in the patient with SHCN include picky eating, compulsive behaviors, restrictive eating (often due to texture), dysregulated eating patterns, lack of access to adaptive physical activity, decreased metabolism, and iatrogenic weight gain (especially antipsychotic medication) [ 28 , 35 , 36 ].…”
Section: The Adolescent With Special Healthcare Needs and Obesitymentioning
confidence: 99%
“…(2016) found adolescents with intellectual disabilities to be respectively 1.54 and 1.80 times more at risk of OW/OB than typically developing adolescents [ 27 ]. African American and Latinx children with disabilities have an even greater risk compared to White children even though overall literature is still limited [ 28 ]. Vigilance to the trajectory of crossing BMI percentiles, whether up or down, in this population can be extremely helpful to identify early changes and rapid intervention for failure to thrive or excessive weight gain [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses have found that exercise can lead to psychosocial improvements [17] as well as improved mental and physical health [18] for members of this population. Participation in judo has been shown to have several benefits for people with ID, ranging from improved social and motor skills [19] to improved cardiovascular health [20].…”
Section: Introductionmentioning
confidence: 99%